Hacking The Geneology and Typology Of Reforming Malay-Nusantara Islamic Thought In Singapore's Al-Imam Magazine (1906-1908) - Alimuddin Hassan Palawa; Agus Miftakus Surur; Dardiri Husni; Masbukin A Rajab; Asmuri Asmuri (NALAR, 2023)
Al-Imam is the first magazine in Persada Alam Melayu-Nusantara that promotes the renewal of Islamic thought and voices the awakening of the backwardness and stagnation of Muslims in this region in the first decade of the 20th century. The managers of Al-Imam magazine claim to be students of Sheikh al-Imam Muhammad Abduh and Rashid Ridha. Thus, in terms of spirit, material, and publishing format, Al-Imam magazine is a "duplication" and "extension" of Al-Manar magazine, which was published by Muhammad Abduh and Rashid Ridha in Cairo, Egypt, from 1898 to 1935. On this basis, the genealogy and typology of the renewal of thought voiced by Al-Imam magazine in the Malay-Nusantara region are based on and get a strong influence from the rational-progressive renewal of Islamic thought by Muhammad Abduh and Rashid Ridha, especially as stated in Al-Manar. Although Al-Imam magazine was only published for two years (1906–1908), its role and influence were very large and wide in this region. The most obvious influence of Al-Imam Magazine is seen in the publication of Al-Munir magazine by Abdullah Ahmad in Padang in 1911–1915.